Hukum, Ilmu Perundang-Undangan dan Peraturan Perundang-Undangan - Anisa Sahara; Tanti Kirana Utami; Puput Intan Permatasari; Rendy Kurniawan; Windi Januarti Setiawan (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
This study explains the relationship between law, legal science, and regulations in building a national legal system that is effective, fair, and responsive to societal needs. As a state based on the rule of law, Indonesia utilizes law as the basis for regulating all aspects of national and state life. Legal science plays a crucial role as a guide in the law-making process, from planning, drafting, deliberation, ratification, and evaluation. This study uses a normative juridical approach by studying various legal theories, such as the Stufenbau des Recht (The Law of Law) by Hans Kelsen and Hans Nawiasky, the theory of law as a tool for community development by Roscoe Pound, and the principles contained in Law Number 13 of 2022 concerning the Formation of Legislation. The results show that legal quality is highly dependent on the application of legal science principles, such as clarity of purpose, transparency, and public participation. However, challenges remain, such as poor coordination between institutions, low-quality academic papers, and minimal public participation in the legislative process. Therefore, the consistent application of legal science is essential to produce legal products that are consistent, non-contradictory, and capable of guaranteeing justice and legal certainty. In conclusion, collaboration between law, legal science, and legislation is key to creating a democratic national legal system based on Pancasila and the 1945 Constitution.